Risk definition and outcomes with the application of the PEGASUS-TIMI 54 trial inclusion criteria to a “real world” STEMI population: results from the Italian “CARDIO-STEMI SANREMO” registry - Sanchez, Federico (BMC Cardiovasc Disord, 2021)
BACKGROUND: The PEGASUS-TIMI 54 trial inclusion criteria effectively identified high-risk patients with recent myocardial infarction (MI) who would benefit from continuing dual antiplatelet therapy (DAPT) with ticagrelor for more than 12 months. It is unknown how many real-world patients meet these criteria during the acute phase of ST-elevation MI (STEMI), or the extent to which these criteria predict a patient's risk and prognosis. Study objectives were: (1) determine the proportion of PEGASUS-TIMI 54-like patients (PG-l) in a real-world cohort of patients hospitalized with STEMI and to assess their ischemic and hemorrhagic risk; (2) examine their ischemic and hemorrhagic in-hospital events (major adverse cardiovascular and cerebrovascular events [MACCE] and clinically relevant bleeding); (3) evaluate their long-term outcomes and the impact on the long-term prognosis of the type of DAPT prescribed at discharge. METHODS: This observational study was conducted in 1086 patients admitted to hospital with a diagnosis of STEMI between February 2011 and March 2018 and enrolled in the CARDIO-STEMI Sanremo registry. Patients’ demographic and clinical characteristics, procedural variables, and individual ischemic and hemorrhagic risk scores were assessed in-hospital. Four-year survival was also analyzed. RESULTS: The proportion of PG-I patients was 69.2%. Compared with non-PG-l patients, PG-l patients were older, had more multivessel disease and comorbidities, and experienced more frequent MACCE (8.3% vs. 3.6%, p = 0.005) and clinically significant bleeding events (6.7% vs. 2.7%, p = 0.008), a higher rate of in-hospital death (6.5% vs. 1.5%, p < 0.001), and higher follow-up mortality rate (14.8% vs. 7.7%; p = 0.002). Four-year survival was significantly lower in the PG-l group (83.9% vs. 91.8%; Log-rank = 0.001) and was related to the cumulative number of concurrent risk factors. In the unadjusted analysis, survival was greater in patients discharged on ticagrelor than on another P2Y(12) inhibitor (90.2% vs. 76.7%, Log-rank = 0.001), and the difference was particularly evident in PG-l patients. CONCLUSIONS: The risk of MACCE for PG-l patients increased with the number of concurrent PEGASUS-TIMI 54 risk features. Treatment with ticagrelor on discharge was associated with improved survival rates during 4 years of follow-up.